2019
DOI: 10.14475/kjhpc.2019.22.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Practitioners’ Perception toward Pediatric Palliative Care in the Republic of Korea

Abstract: This study was performed to investigate the current status of pediatric palliative care provision and how it is perceived by the palliative care experts. Methods: A descriptive study was conducted with 61 hospice institutions. From September through October 2017, a questionnaire was completed by experts from the participating institutions. Data were analyzed using SPSS 21.0. Results: Among 61 institutions, palliative care is currently provided for pediatric cancer patients by 11 institutions (18.0%), all of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…This study is significant in that a workbook was developed for the context of the South Korean medical field based on advance care planning workbooks for children and adolescents used abroad, and the quality of the workbook content was enhanced by creating separate versions for children and adolescents. It was found that the workbook could be utilized that is often avoided due to the uncertainty of the prognosis and the negative perceptions of patients and caretakers [27], but it is meaningful for child and adolescent patients to have the freedom to express their own values about life and death through completing the workbook. Lastly, the results of this study suggest necessary considerations and behavioral guidelines for using the workbook and can be used as foundational data at children's hospitals or other institutions that require discussions about advance care planning with children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…This study is significant in that a workbook was developed for the context of the South Korean medical field based on advance care planning workbooks for children and adolescents used abroad, and the quality of the workbook content was enhanced by creating separate versions for children and adolescents. It was found that the workbook could be utilized that is often avoided due to the uncertainty of the prognosis and the negative perceptions of patients and caretakers [27], but it is meaningful for child and adolescent patients to have the freedom to express their own values about life and death through completing the workbook. Lastly, the results of this study suggest necessary considerations and behavioral guidelines for using the workbook and can be used as foundational data at children's hospitals or other institutions that require discussions about advance care planning with children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Health care providers revealed that the main barriers to PPC in South Korea are poor understanding of the unique needs of children with LTC and their families, a lack of professionals skilled in PPC, and restricted eligibility for hospice services that make patients choose either disease-focused treatment or PPC. 13,14 In South Korea, distinct palliative care services for children did not exist until 2018, and the preliminary results of this study contributed to initiating a PPC pilot service, a consultation-based specialized care integrated with disease-oriented treatment for children with LTC and their families, regardless of their diagnosis. Therefore, it is necessary to understand the needs of children with LTC and their families, the care recipients for PPC encompassing diagnostic groups (cancer or noncancer), and illness trajectory (parents actively caring for a child with LTC or bereaved parents who have lost their child) to develop needbased, quality PPC services.…”
Section: Introductionmentioning
confidence: 96%
“…However, access to PPC was still limited, and studies were conducted to understand the needs and barriers to PPC. Health care providers revealed that the main barriers to PPC in South Korea are poor understanding of the unique needs of children with LTC and their families, a lack of professionals skilled in PPC, and restricted eligibility for hospice services that make patients choose either disease-focused treatment or PPC 13,14 …”
mentioning
confidence: 99%
“…Ongoing pilot projects in pediatric palliative care have been in place at 10 institutions in Korea since 2018 [1]. However, there are still a variety of difficulties in appropriately providing pediatric palliative care services [2,3]. Pediatric palliative care involves the collaboration of interdisciplinary team members, including physicians, nurses, social workers, art therapists, spiritual interventionists, and volunteers, who provide fundamental services [4].…”
Section: Introduction 1 Backgroundmentioning
confidence: 99%